LIVER MORPHOGENESIS IN FIRST-GENERATION RATS BORN TO FEMALES WITH INDUCED DIABETES MELLITUS DURING EARLY POSTNATAL ONTOGENESIS - Azizova F.Kh., Ubaydullayeva M.A., (Central Asian Journal of Medicine, 2025)
Background: The liver plays a critical role in metabolism, detoxification, hematopoiesis, and immune defense. The impact of maternal diabetes mellitus on liver histogenesis during early postnatal ontogenesis remains insufficiently studied, despite the increasing prevalence of diabetes among women of reproductive age and data indicating its effect on the development of fetal parenchymal organs. Methods: The experimental study was conducted on 50 white outbred female rats (25 control, 25 experimental) with diabetes induced by a single intraperitoneal injection of alloxan (13 mg/100 g). Offspring (n=253) were examined on postnatal days 3, 7, 14, 21, and 30. Histological liver examination was performed using hematoxylin and eosin staining, and morphometric analysis was carried out with QuPath 0.5.1 software. Parameters assessed included lobule area and diameter, hepatocyte and nuclear dimensions, mitotic count, nuclear-cytoplasmic ratio, and fibrotic changes. Results: In the control group, liver tissue demonstrated progressive formation of beam and vascular architecture, bile duct maturation, and a reduction in mitotic activity by day 30. The experimental group exhibited disorganized beam structure, persistent cytoplasmic vacuolization in hepatocytes, delayed development of portal tracts, and increased numbers of mitoses and binuclear cells. Morphometry showed significantly larger lobule and hepatocyte dimensions and moderate collagen accumulation in portal areas (p<0.001). Conclusion: Maternal diabetes mellitus has a significant negative effect on liver morphogenesis in offspring during early postnatal ontogenesis, manifested by delayed differentiation, architectural disorganization, and early signs of fibrosis.